HUBUNGAN ANTARA HARGA DIRI DENGAN PENCAPAIAN SUCCESSFUL AGING PADA LANSIA WANITA DI DESA KARANGTENGAH - Raras Anggun Atika Candra; Eva Rahayu; Made Sumarwati (Kesmas Indonesia, 2016)
The changes in physical, psychological and social condition in the elderly can lead to the emergence of feelings of worthlessness, helplessness and uselessness that may influence their self-esteem. Physical, psychological and social condition in elderly women in Indonesia indicated a lower quality compared with elderly men. Self-esteem has influence on psychological well-being required to achieve successful aging. This research aimed to determine a positive relationship between self-esteem and achievement of successful aging on elderly women in Karangtengah village.This research was a quantitative research using cross sectional study design. The sample in this research was 142 elderly women selected by using simple random sampling technique. Data were collected using a questionnaire of Rosenberg Self-Esteem Scale and Successful Aging Scale. Data analysis in this research used Spearman test. The result of correlation test indicated that there was a statistically very strong positive relationship between self-esteem and achievement of successful aging on elderly women in Karangtengah village (r=0.866, p=0.000). Furthermore, the result of correlation test also indicated that there was a statistically positive relationship between self-esteem and the aspects of successful aging, such as a functional well (r=0.660, p=0.000), psychological well-being (r=0.539, p=0.000), selection, optimization and compensation (r=0.607, p=0.000) as well as primary and secondary control (r=0.705, p=0.000). High selfesteem can improve the achievement of successful aging on elderly women in Karangtengah village.